EFFICIENCY OF CHEMICAL PREPARATIONS AGAINST OF EUROPEAN CORN BORER - Nosirova Z.G’.; Abdusamatov Asror Akbar o‘g‘li; Ummatov Laziz Mamayun o‘g‘li; Latiboyeva Dilfuza Marufjon qizi (Web of Journals Publishing, 2024)
The analysis of field experiences carried out on revealing efficiency of chemical preparations against of European corn borer (Ostrinia nubilalis, Hubner) has been presented. As the chemical preparations “Deluxe Ultra” (10% em.c.), produced by “Top Trade Plyus” company limited (Uzbekistan), “Fufanon” (57% em.c.), produced by “Keminova A/C” firm (Denmark), “Double D” (55% em.c.), produced by “Agrokim” company limited (Uzbekistan) have been chosen and in the open field conditions have been tested. Then the selected for experiences areas with chosen preparations have been treatment two times, which the earlier and later treatments have been called, correspondingly. It has been revealed that the values of the biological efficiency have a rising character in each types of chosen preparations. The most reached efficiency, 95.6%, in the earlier treatment with “Double D” preparation after 5 days of treatment was observed, which after the later treatment was decreased a bit down to 87.6%. The biological efficiency in case of the later treatment was equaled to 100%, that is beginning from this day up to end of the season not a single butterfly of European corn borer was encountered. This situation showed that the used preparations are effective enough in fight against of European corn borer.
Keywords: European corn borer, chemical preparations, biological efficiency.